2016
DOI: 10.1111/ctr.12738
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir and simeprevir without ribavirin effectively treat hepatitis C virus genotype 1 infection after liver transplantation in a two‐center experience

Abstract: Sofosbuvir + SIM combination therapy without ribavirin is well tolerated and results in high virologic response rates in recurrent HCV GT1 infection after liver transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Except one study that did not report patient ethnicity, the majority of patients were Caucasian, male, with a mean age of approximately 60‐year‐old, had GT1a HCV recurrence, and received tacrolimus as part of their immunosuppressive treatment. Five different DAA combination protocols were described: SOF/SMV with or without RBV (n = 8); SOF/LDV (n = 3); ASV/SMV (n = 2); DCV/SMV with or without RBV (n = 2); PrOD (n = 1) . Detailed baseline characteristics of the included studies are provided in Tables and .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Except one study that did not report patient ethnicity, the majority of patients were Caucasian, male, with a mean age of approximately 60‐year‐old, had GT1a HCV recurrence, and received tacrolimus as part of their immunosuppressive treatment. Five different DAA combination protocols were described: SOF/SMV with or without RBV (n = 8); SOF/LDV (n = 3); ASV/SMV (n = 2); DCV/SMV with or without RBV (n = 2); PrOD (n = 1) . Detailed baseline characteristics of the included studies are provided in Tables and .…”
Section: Resultsmentioning
confidence: 99%
“…In current study, we observed an increased pooled estimate incidence rate of sAEs in patients treated with RBV, in accordance with the results from previous studies. Given that a number of studies have pointed out RBV were not correlated with an increased SVR12 rate, we compared patients treated or not treated with this medication. Our results also indicated that RBV was not correlated with an increased pooled estimate SVR12 proportion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 As a matter of concern, sofosbuvir-based regimens are associated with changes in renal function between treatment onset, end of treatment (EOT) and/or end of follow-up. [1][2][3][4][5][6][7] It is not clear whether these modifications are a sign of renal toxicity or not. Serum creatinine and the estimated glomerular filtration rate (eGFR) are widely used to appreciate changes in renal function over time but have limitations.…”
Section: Introductionmentioning
confidence: 99%